RANCANG BANGUN APLIKASI MOBILE WEB UNTUK MARKETPLACE KLINIK HEWAN - Anjani Putri, Adisti; Kristina Prajnyawati, Rahel; Arsa Suyadnya, I Made; Shandyasa, I Wayan (Jurnal SPEKTRUM; Vol 10 No 3 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i03.p11, 2023)
Pet owners rely on veterinary clinics to meet the healthcare needs of their pets, and yet, many veterinary clinics still manage data using conventional methods without fully utilizing digital information systems. This leads to issues such as repetitive registration, difficulties in obtaining copies of medical records, and challenges in finding nearby veterinary clinics. This research aims to address these problems by designing and developing a mobile web application for a veterinary clinic marketplace. The application consists of two main components. The front-end utilizes the React.js library based on Progressive Web Apps (PWA), while the back-end utilizes the Express.js framework. To ensure the overall functionality of the application, black box testing is conducted by the developer. Through this approach, the application is expected to assist pet owners in searching for and accessing information about veterinary clinics, viewing the services provided, and managing pet medical records digitally and easily. This research contributes to optimizing data management in veterinary clinics and enhancing the experience of pet owners.